Owls, larks, or investment sharks? The role of circadian process in early-stage investment decisions - Guarana, Cristiano L.; Stevenson, Regan M.; Jeffrey Gish, J.; Ryu, Ji Woon; Crawley, Rohan (Journal of Business Venturing, 2022)
Investors in early-stage companies want to detect and select high-potential opportunities to maximize their long-term returns. However, in uncertain and risky early-stage investment contexts, company information is often opaque, and decision-making timeframes are compressed. Although there is an abundance of prior work on how investors make structured decisions based on their experience and expertise, there is a very limited understanding of how time-based factors can sway investment decisions. The circadian process is the 24-hour sequence that serves as an individual's internal timer influencing not only sleep cycles, but also attention and performance on a wide range of cognitive tasks. Understanding how the circadian process impacts early-stage investment holds implications for optimal investment decisions. We build on social cognitive theory and propose that investor-level factors (i.e., chronotypes) and environmental factors (time of the day) interact to influence the amount of information investors search for, and consequently, their investment decisions. We hypothesize and find that investors are influenced by the time of day they make early-stage investment decisions. Lark investors make better investment decisions in the morning, whereas owl investors make better decisions in the evening. Information search effort mediates this relationship.